Factors for Abortion Seeking Among Women Attending Health Facilities - Amatya, A (Journal of Nepal Health Research Council, 2011)
Background: Unsafe abortion contributes to high maternal mortality in the country which is 281 per 100,000 live births. In line with the expansion of safe abortion services to all 75 districts, it was time for us to look into the depths of the determinants that lead women to seek abortion. Methods: A cross-sectional descriptive study was conducted in three centers providing safe abortion services in Kathmandu valley, viz. Paropakar Maternity and Women’s Hospital, Marie Stopes International (MSI), Nepal, at Sat Dobato and Tribhuvan University Teaching Hospital (TUTH) from 16th July to 31st August 2009. A total of 450 respondents were interviewed, out of them 270 (60%) were from public centers and 180 (40%) from INGO run centers. Results: It was observed that 32% of the respondents were in the group of 25-29 years;more than a third (34.9%) of the respondents was pregnant for the third time;58% were using some kind of contraceptive prior to this pregnancy and 90.4% showed a desire to use some kind of contraceptive after the abortion. The main reasons cited for termination were completed desired family size and mistiming and 101 (22.4%) had a history of previous induced abortion. Conclusions: There was a significant association between the uses of contraceptive methods prior to the index pregnancy in women who had sought previous induced abortion and it was also seen that women having previous termination had completed their desired family size of two and the age of the last child was above five. Keywords: contraceptive, induced abortion, repeat abortion, safe abortion services.